2002
DOI: 10.1590/s1516-93322002000200011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do uso de medicamentos na rede pública municipal de saúde de Campo Grande/MS

Abstract: Em virtude do arsenal terapêutico disponível às populações, é crescente no âmbito mundial a preocupação com o uso racional dos medicamentos. Estudos de Utilização de Medicamentos, atividade da Farmacoepidemiologia, fornecem importantes informações sobre todas as fases do uso dos fármacos em uma sociedade e suas conseqüências, evidenciando como é feita a gestão saúde/doença. Neste estudo objetivou-se avaliar o uso de medicamentos na rede pública municipal de saúde de Campo Grande/MS, empregando a metodologia pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
35

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 1 publication
2
10
1
35
Order By: Relevance
“…National publications about household-level medicine access are scant, the methodologies employed vary, access is measured regardless of consumption conditions 15,16,17,18 and some studies exclude chronic patients 14 . Other studies have evaluated medicine access based on the availability of medicine in health services 2,3,4,5,19 . In spite of different methods, population studies using 15-day recall period report medicine access ranging from 87% to 96% 14,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…National publications about household-level medicine access are scant, the methodologies employed vary, access is measured regardless of consumption conditions 15,16,17,18 and some studies exclude chronic patients 14 . Other studies have evaluated medicine access based on the availability of medicine in health services 2,3,4,5,19 . In spite of different methods, population studies using 15-day recall period report medicine access ranging from 87% to 96% 14,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Emmerick et al 20 , in a study carried out in 5 Brazilian states, reported that the national average for the percentage of prescribed drugs dispensed or administered was 67.9%, varying from 89.6% in Espírito Santo to 52.6% in Rio Grande do Sul, considering the state and from 22.0% to 93.2% considering health units analyzed. Other authors report values varying from 60.3% to 80.7% of the prescribed drugs being met 19,[25][26][27] and describe problems to calculate the indicator due to lack of dispensing annotation when supply occurs, different patterns of annotation between employees, dispensing of non-standard medicines due to free samples or donations or not yet retaining the second way of prescription, compromising data collection. Since data collection was performed at the time of dispensing, not depending on retention of the second way or annotation, the problems reported in the calculation of the indicator were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of prescription varied in studies conducted in other cities, and according to the methodology, ranging from 34% to 70% 25,26,31 . However, a visual identification system with the use of standardized colors and print-outs allowed the majority of patients to adequately comply with the medication prescription -according to the patients' reports -without the need for direct action of the pharmacist.…”
Section: Discussionmentioning
confidence: 99%
“…O percentual de medicamentos prescritos presentes nas REMUME apresentou variações importantes entre os municípios (25,7% a 92,9%), com percentual médio de 76,4%. Em estudos anteriores, os percentuais variaram de 58,4% a 92,7% 11,12,13,14,15,16,17 . O percentual verificado também é inferior aos observados em países da África, que variaram entre 88% e 92,3% 18,19,20,21 e Ásia, com 85% a 99,7% 18,22,23,24 .…”
Section: Discussionunclassified
“…Entre os elementos que compõem o acesso, indicadores de disponibilidade dos medicamentos nos serviços têm sido investigados, com variações conceituais entre os pesquisadores. Para análise da disponibilidade de medicamentos-chave, Naves & Silver 14 e Cunha et al 12 utilizaram uma lista de quarenta medicamentos considerados marcadores, conforme metodologia proposta pela OMS. Em outro estudo de abrangência nacional, foi verificada disponibilidade de 73% para uma lista de 15 medicamentos considerados principais, além de contraceptivo oral e preservativo masculino, em 29 unidades de saúde, pertencentes a cinco capitais brasileiras e outros cinco municípios menores 10 .…”
Section: Discussionunclassified